Religion in vogue : Christianity and fashion in America - Neal, Lynn S. (New York University Press, 2019)
How the fashion industry has contributed to religious change From cross necklaces to fashion designs inspired by nuns' habits, how have fashion sources interpreted Christianity? And how, in turn, have these interpretations shaped conceptions of religion in the United States? Religion in Vogue explores the intertwined history of Christianity and the fashion industry. Using a diverse range of fashion sources, including designs, jewelry, articles in fashion magazines, and advertisements, Lynn S. Neal demonstrates how in the second half of the twentieth century the modern fashion industry created an aestheticized Christianity, transforming it into a consumer product. The fashion industry socialized consumers to see religion as fashionable and as a beautiful lifestyle accessory--something to be displayed, consumed, and experienced as an expression of personal identity and taste. Religion was something to be embraced and shown off by those who were sophisticated and stylish, and not solely the domain of the politically conservative. Neal ultimately concludes that, through aestheticizing Christianity, the fashion industry has offered Americans a means of blending traditional elements of religion--such as ritual practice, miraculous events, and theological concepts--with modern culture, revealing a new dimension to the personal experience of religion.